How to optimize the cost and time of the acquisitions process?. Issue 2 (7th April 2015) - Kont, Kate-Riin
Abstract : Purpose: – The purpose of this paper is to focus on the history and new developments of the optimization and analysis of acquisitions costs. More specifically, the acquisition cost and time optimization methods studied concern primarily print format books. Though e-books have begun to be developed more and more, the print format books – both scientific books and textbooks – are still very important for university libraries and continue to pour into acquisition activities. Design/methodology/approach: – The data used in this paper are based on a review of relevant literature to provide an overview of the different concepts of the budget allocation and cost accounting methods suitable for the optimizing cost and time of the acquisition process. Different methods are described via reviewing example studies. Findings: – On the basis of the current study, it can be said that the acquisitions procedure is more labor-intensive than any other library procedure both historically and nowadays. Nonetheless, the routines of acquisitions have been fairly well fixed over the years and constantly have searched for new ways to reduce costs. The most popular methods to control the acquisitions budget have been centralized and cooperative acquisitions, using vendors for acquiring library materials, customer-based acquisitions, and price indexes. New costing methods described, like activity-based costing and time-driven activity-based costing methodologies seem both to be the best tools for understanding acquisitions cost behavior and for refining a cost system for university libraries. Originality/value: – This paper raises a perspective in library acquisitions management that has not been dealt with before. Namely, it explores how the library materials selection moved from intrinsic wisdom of bookish librarians and "just in case" inventory model to "purchase by customer suggestion" model. In addition, how libraries moved from acting on the basis of guesses to examine the cost breakdown of the acquisitions-related activities in a library.